Youth Engagement Strategies in Citarum River Cleanup Campaigns via Instagram: A Mixed-method Content Analysis - Cipta Endyana; Yunus Winoto; Evi Novianti; Eldo Delamontano (INJECT (Interdisciplinary Journal of Communication), 2025)
This study explores how Instagram is utilized as a strategic communication tool to campaign for environmental engagement, specifically in promoting river cleanup initiatives among youth audiences. By employing a quantitative content analysis of eleven Instagram posts related to river cleanup efforts conducted between December 2024 and June 2025, we examine audience interaction metrics such as views, reach, likes, and engagement across different age groups. The findings highlight that the 18–34 age demographic is the most responsive to environmental messaging on social media, accounting for over 70% of total engagement. Posts featuring direct community involvement, promotional content, and educational messaging were identified as key content pillars driving higher interaction rates. These pillars demonstrate the importance of message framing in digital environmental advocacy. The study affirms Instagram’s potential as an effective platform for fostering eco-conscious behavior and youth participation through visual storytelling and targeted communication strategies.